PENGARUH CARRENT RATIO,DEBT TO EQUIYY RATIO DAN RETURN ON ASSET TERHADAP RETURN SAHAM PADA PERUDAAN YANGTERGABUNG DALAM INDEKS BISNIS 27 - Piter nainggolan (Universitas Bunda Mulia, 2017)
financial statemen report,information system that provided report to stakeholders about the economic activity an condition of abusiniss.Curren ratio,debt to equity ratio and return on assat relevan information was significant innfluencial to shareon return.Key word:Current ratio,Debt to Equity ratio,Return on asset and Share on return